Numerical and experimental studies of convection heat transfer to nanofluids in closed conduit flow / Mohammad Reza Safae - Mohammad Reza , Safae (2015)
Application of nanofluids in heat transfer enhancements is prospective. They are well-suited to heat transfer. A number of studies on the effect of nanofluids in heat transfer have been conducted in order to determine the enhancement of properties in addition to rearrangement of flow passage configurations. The principal objective of the present study is to elaborate the natural, forced and the mixed convection heat transfer characteristics of nanofluids. This work is presented an experimental as well as numerical study of heat transfer to laminar and turbulent flow of distilled water and distilled water-ethylene glycol (as base fluid) and multi-walled carbon nanotube (MWCNT) and copper (as nanoparticles) nanofluids inside different types of closed conduits. The Finite Volume Method was used through FLUENT software (for two-phase mixture as well as discrete phase models) and two in-house FORTRAN codes (for single phase model) to solve the governing equations. The model predictions were found to be in good agreement with previous experimental and numerical studies. The Thermo-physical properties of nano-fluids, including the thermal conductivity and viscosity, were experimentally measured at various concentrations and applied into the numerical section to enhance the accuracy of simulation. By doing this, deviation related to the estimation of thermo-physical properties, approaches to the minimum value. At the same time, the convective heat transfer coefficient and friction factor for fully developed turbulent flow of multi-walled carbon nanotube-based nanofluids flowing through a sudden expansion with a contraction ratio of 2 was determined experimentally. To validate the reliability and repeatability of the experimental data, several tests were conducted for distilled water. In the present study, the effects of nanoparticle type and concentration, inlet velocity (Reynolds number), heat flux, closed conduit configuration and turbulence on the hydraulics and thermal behavior of nanofluid flow was studied experimentally and numerically. The results indicated that for a closed conduit, the Reynolds number and nanoparticle volume fraction considerably affect the heat transfer coefficient; a rise in local heat transfer coefficient has been noted when both Reynolds number and nanoparticle volume fractions are increased for all cases. That’s while, in a constant Reynolds number, heat flux augmentation did not have any significant influence on heat transfer and fluid flow parameters.